Emergence of carbapenemase-producing Enterobacterales (CPE) in patients with severe COVID-19 infection and successful control in intensive care - Anthony Longhitano; Duncan Campbell; Nomvuyo Mothobi; Alison McKenzie; Caroline Bartolo; Sajal Saha; Norelle Sherry; Eugene Athan (Cambridge University Press, 2024)
Abstract Objective: We aim to highlight the risks of acquiring carbapenemase-producing Enterobacterales (CPE) resistance genes in patients with severe coronavirus disease 2019 (COVID-19) in intensive care. Design: Outbreak analysis to assess for a transmission risk area (TRA) conducted after identification of potential CPE outbreak within shared room spaces in intensive care. Setting: Analysis conducted within a 24-bed single-room model intensive-care department within a level-3 tertiary center public hospital in regional Victoria, Australia. Patients: 3 patients, with severe COVID-19 admitted to intensive care over a 3-month period with shared room spaces requiring prolonged mechanical ventilation and broad-spectrum antimicrobials, identified and were managed for CPE isolated from sputum. Overlap carbapenemase genes were identified among different organisms raising suspicion of transmitted resistance genes. A subsequent case managed for severe community-acquired pneumonia isolated CPE 3 months beyond these cases. Methods: Outbreak analysis via weekly cross-sectional point prevalence screening of fecal samples or rectal swabs for CPE from patients admitted to the intensive-care department over a 4-week period. Results: 34 patients were included in the analysis with 51 tests for CPE screening conducted. No further cases of CPE were identified. Statewide Infection Surveillance team and the Department of Health and Human Services did not find the cases to derive from a TRA. No further action including environmental screening was indicated. Conclusions: These cases highlight the independent acquisition of CPE genes in patients with severe COVID-19 and antimicrobial selective pressures resulting in significant morbidity and mortality. Increasing awareness, robust antimicrobial stewardship, and infection prevention measures could reduce pressures driving CPE resistance mutations and the risk of CPE transmission.